Pengaruh Regulasi Diri dan Lingkungan Belajar terhadap Prestasi Belajar Matematika Siswa - Baso Akbar; Thamrin Tayeb; Ahmad Afiif; Munirah; Munawarah (Alauddin Journal of Mathematics Education, 2022)
The purpose of this study is to determine the picture of self-regulation in mathematics subjects, an overview of the learning environment, an overview of student mathematics learning achievement, and the influence of self-regulation and learning environment on the mathematics learning achievement of class VIII MTsN Model Makassar students. This research is a quantitative study using an Ex-post facto design. The population in this study was all students of class VIII MTsN Model Makassar which amounted to 386 people, with a total sample of 97 students. This study uses instruments in the form of self-regulation scales, learning environment questionnaires and documentation and uses descriptive statistical analysis techniques and inferential statistical analysis with Multiple Linear Regression analysis techniques. The results showed the influence of self-regulation on the achievement of learning mathematics for class VIII MTsN Model Makassar students, the influence of the learning environment on the achievement of learning mathematics for class VIII MTsN Model Makassar students and the simultaneous influence of self-regulation and learning environment on the achievement of mathematics learning for students of class VIII MTsN Model Makassar. The results of the descriptive statistical analysis obtained an average student self-regulation of 74.69 in the moderate category, a learning environment of 9.56 in the moderate category and student mathematics learning achievement of 78.29 was in the medium category. Based on the results of statistical testing obtained the regression equation Y = 72.144 + 0.067X1 + 0.123X2. Hypothesis tests showed Fhitung >Fable (6.803 > 3.94), so H0 was rejected. With the rejection of H0 then H1 is accepted. Thus, it can be concluded that self-regulation and the learning environment affect students' mathematics learning achievement.